Analysis of Economic Potentials and Their Impacts on Growth in Gresik Regency - Naibaho, Messi Valensiana; Moh. Athoillah (Journal of Development Economic and Social Studies, 2025)
The slowing economic growth of Gresik Regency over the past decade, despite a surplus trade balance and industrial dominance, reveals underlying structural challenges such as economic inequality and signs of early deindustrialization. This study aims to identify the base sectors, examine their contributions to economic growth, and formulate strategies to optimize their potential in accelerating regional development. Employing quantitative methods, this research utilizes Location Quotient (LQ) to identify base sectors, Shift-Share Analysis to assess sectoral contributions, and the Growth Ratio Model (MRP) to evaluate development potential. The findings highlight that manufacturing, mining and quarrying, and electricity and gas supply are key base sectors, while construction and wholesale-retail trade, though not base sectors, show strong growth potential. Challenges such as global competition and regulatory constraints hinder sectoral performance. The study concludes that a comprehensive strategy involving economic diversification, investment enhancement, human capital development, and technology adoption is crucial for sustainable growth. These findings provide practical implications for policymakers in fostering inclusive and resilient economic development in Gresik Regency.